2006
DOI: 10.1117/12.654589
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of corrosion damage to steel reinforced mortar using frequency sweeps of guided mechanical waves

Abstract: A frequency sweep from 50 to 200 kHz of guided mechanical waves have been conducted to detect and assess corrosion damage in steel reinforced mortar specimens with seeded defects and in specimens undergoing accelerated corrosion using impressed current. The sweep was conducted by invoking primarily the fundamental longitudinal mode of propagation, i.e., the L(0,1) mode. The decay of waveform energy (indicative of attenuation) at different frequencies is presented and discussed in terms of corrosion damage. Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…As stated earlier, corrosion of steel reinforcement bars can produce waste materials that occupy between two and six times the volume of the original steel [2]. When the expansion-induced stresses exceed the tensile strength of the concrete, cracking and other defects occur, in addition to the loss in cross-sectional area of the rebar.…”
Section: A Corrosion Of Steel Reinforcing Bars ("Rebars")mentioning
confidence: 97%
See 1 more Smart Citation
“…As stated earlier, corrosion of steel reinforcement bars can produce waste materials that occupy between two and six times the volume of the original steel [2]. When the expansion-induced stresses exceed the tensile strength of the concrete, cracking and other defects occur, in addition to the loss in cross-sectional area of the rebar.…”
Section: A Corrosion Of Steel Reinforcing Bars ("Rebars")mentioning
confidence: 97%
“…However, a major issue for reinforced concrete structures is the corrosion of the rebars under aggressive environmental conditions, such as exposure to chlorides. The corrosion of rebars can lead to the creation of waste materials, which occupy many times the volume of the original steel [2], [3]. The effect of which is to severely compromise the integrity of the structure-occasionally leading to catastrophic structural failure.…”
Section: Introductionmentioning
confidence: 99%
“…Ervin and Reis [42] and Ervin et al [55] used both low (<200 KHz, (0, 1) mode) and high [2-9 MHz, (0, 9) mode) guided longitudinal modes for monitoring corrosion in reinforced mortar by the accelerated corrosion experiments. It was found that surface-seeking modes were sensitive to the combined effect of bond deterioration and mortar stiffness reduction while core-seeking modes related well to change in cross-sectional area of the reinforcement.…”
Section: Monitoring Combined Effects In Actual Corrosionmentioning
confidence: 99%
“…The effect of ribs on a ribbed bar can be ignored when the ratio of the diameter and the length is less than 0.4 [8].…”
Section: Dispersion Curves Of Ugw Propagation In Steel Rebarmentioning
confidence: 99%
“…This characteristic is especially suitable to detect long range bridges. Guided waves were chosen because of the possibility of analyzing guided wave behavior in certain frequency ranges to distinguish between the loss of bar cross-sectional area and change of interface conditions [8]. High sensitivity is another merit of this 2 International Journal of Distributed Sensor Networks method.…”
Section: Introductionmentioning
confidence: 99%